2000
DOI: 10.2135/cropsci2000.4041062x
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Cultivar Differences in Ureides and the Relationship to Drought Tolerant Nitrogen Fixation and Manganese Nutrition

Abstract: Water deficit in soybean [Glycine max (L.) Merr.] results in the accumulation of the products of N2 fixation (ureides) in shoots, and this may lead to feedback inhibition of N2 fixation. Manganese is required for ureide degradation in leaves, and it was hypothesized that increased leaf Mn+2 would alleviate ureide accumulation during drought, lessen feedback inhibition, and prolong N2 fixation. In a growth chamber experiment, ureides supplied through roots decreased N2 fixation in well‐watered plants, and a soy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
77
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(85 citation statements)
references
References 21 publications
8
77
0
Order By: Relevance
“…Interestingly, our work showed that there was a major interaction between Mn nutrition and the decline of nitrogen fixation under water deficit [28], in agreement with the data of Purcell, King and Ball [16]. Indeed, a Mn application allowing a leaf Mn concentration of about 21 to 32 mg⋅kg -1 delayed the decline of nitrogenase activity induced by water deficit, which appeared to be linked to an increased leaf Mn availability, leading to an enhanced rate of in situ ureide degradation.…”
Section: Mn Application Delays the Drought Inhibition Of N 2 Fixationsupporting
confidence: 92%
See 1 more Smart Citation
“…Interestingly, our work showed that there was a major interaction between Mn nutrition and the decline of nitrogen fixation under water deficit [28], in agreement with the data of Purcell, King and Ball [16]. Indeed, a Mn application allowing a leaf Mn concentration of about 21 to 32 mg⋅kg -1 delayed the decline of nitrogenase activity induced by water deficit, which appeared to be linked to an increased leaf Mn availability, leading to an enhanced rate of in situ ureide degradation.…”
Section: Mn Application Delays the Drought Inhibition Of N 2 Fixationsupporting
confidence: 92%
“…Because of Mn's role in the ureide degradation in soybean leaves, Purcell, King and Ball [16] hypothesized that Mn might regulate nitrogen fixation under water deficit. Interestingly, our work showed that there was a major interaction between Mn nutrition and the decline of nitrogen fixation under water deficit [28], in agreement with the data of Purcell, King and Ball [16].…”
Section: Mn Application Delays the Drought Inhibition Of N 2 Fixationmentioning
confidence: 99%
“…Higher accumulation of Mn in the NFDT genotype R01-581F suggests a further attribute inherited from 'Jackson'. Manganese-dependent metabolism of ureides suggests that higher levels of Mn in leaves may help soybean to cope with accumulation of ureides in shoots under drought (Purcell et al, 2000). Although Vadez and Sinclair (2002) observed the same trend, there is evidence that the enzymatic degradation of ureides in 'Jackson' may not require Mn as a cofactor.…”
Section: Discussionmentioning
confidence: 94%
“…Climate changes are expected to reduce rainfall in subtropical areas by 20 % (IPCC, 2007), increase the frequency of drought and cause losses to soybean crop yields. Studies have indicated that the combination of three mechanisms may impair the BNF under drought: (1) limitation of oxygen supply to nodules (King and Purcell, 2001); (2) shortage of carbon supply to bacteroids due to reductions in the activity of sucrose synthase (SS) (Arrese-Igor et al, 2011); and (3) regulation of N metabolism by feedback of N compounds, mainly ureides (Purcell et al, 2000;Collier and Tegeder, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Mn leaf accumulation has been shown to be related to certain aspects of drought tolerance in soybean (Purcell et al, 2000;Vadez and Sinclair, 2002;Sinclair et al, 2007) and cotton (Weil et al, 1997). Very few results have been published on the relationship between Mn status and drought tolerance in maize genotypes (De et al, 2004).…”
Section: Introductionmentioning
confidence: 99%